2003
DOI: 10.1029/2002pa000872
|View full text |Cite
|
Sign up to set email alerts
|

A deglacial–middle Holocene record of biogenic sedimentation and paleoproductivity changes from the northern Norwegian continental shelf

Abstract: The relative proportions of marine organic carbon and biogenic carbonate in a high‐resolution record from a glacial trough on the northern Norwegian continental shelf were used to decipher changes in biogenic sedimentation and paleoproductivity from the last deglaciation to the middle Holocene. Decadal‐scale to century‐scale oscillations in biogenic sedimentation and surface ocean productivity recorded in the Andfjorden sediments are synchronous with abrupt climate changes in open oceanic and atmospheric regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 78 publications
2
36
0
Order By: Relevance
“…With the highly fluctuating sedimentation rates and an inadequate number of AMS 14 C dates, documentation of proxy records as accumulation rates is not recommended. As Knies et al (2003) pointed out, bulk and compound-specific accumulation rates in the Andfjord simply follow the jumps in linear sedimentation rates, owing to the low resolution of the age model, and would therefore distort interpretation of biogeochemical processes and their changes from bulk and molecular geochemical data. Because linear sedimentation rates are often higher and more variable in coastal and shelf settings than the concentration of a given compound (e.g., sterols, alkenones), calculation of accumulation rates only makes sense if a well constrained and high-resolution age model is available.…”
Section: Core Location and Chronologymentioning
confidence: 96%
See 2 more Smart Citations
“…With the highly fluctuating sedimentation rates and an inadequate number of AMS 14 C dates, documentation of proxy records as accumulation rates is not recommended. As Knies et al (2003) pointed out, bulk and compound-specific accumulation rates in the Andfjord simply follow the jumps in linear sedimentation rates, owing to the low resolution of the age model, and would therefore distort interpretation of biogeochemical processes and their changes from bulk and molecular geochemical data. Because linear sedimentation rates are often higher and more variable in coastal and shelf settings than the concentration of a given compound (e.g., sterols, alkenones), calculation of accumulation rates only makes sense if a well constrained and high-resolution age model is available.…”
Section: Core Location and Chronologymentioning
confidence: 96%
“…The samples were freeze-dried, carefully ground, and stored for another four weeks at Ϫ30°C prior to organo-geochemical analyses. The age of the cored sediment was published by Knies et al (2003) and later revised by Ebbesen and Hald (2004). A suite of nine calibrated accelerator mass spectrometry (AMS) 14 C dates and the detection of the Vedde Ash at 436.5 cm (10.31 14 C ka; Birks et al, 1996) were used to establish the age model by linear interpolation (Table 1).…”
Section: Core Location and Chronologymentioning
confidence: 99%
See 1 more Smart Citation
“…years B.P., and correlated this peak to the Greenland GRIP ice core 8200 years event. Knies et al (2003) reported two prominent lows in marine organic carbon in Andfjorden that may correlate with the Preboreal Oscillation (PBO; 11.17-11.05 ka) and the Greenland 8.2 ka event, as discussed by Bjö rck et al (1996) and Alley et al (1997), respectively. The PBO is probably also present in our data (Fig.…”
Section: The 82 Ka Cooling Eventmentioning
confidence: 99%
“…Al, Fe, Ti and Si) indicates marine carbonate productivity to be the main calcite and Ca source in all three fjords. However, we note that to confirm this assumption it is necessary to investigate the organic components (such as C org and 13 C org ) of the sediments samples to distinguish the marine and terrigenous origin of Ca (Faust, 2014;Knies et al, 2003). Nevertheless, the increase in Ca/Al from the inside towards the entrance of the Ofot-and Tysfjord fjords (Fig.…”
Section: Ca and Calcite: Marine Productivity Proxiesmentioning
confidence: 99%